1991
DOI: 10.1021/bc00012a006
|View full text |Cite
|
Sign up to set email alerts
|

Antibody labeling with copper-67 using the bifunctional macrocycle 4-[(1,4,8,11-tetraazacyclotetradec-1-yl)methyl]benzoic acid

Abstract: The high kinetic stability of the Cu2+ complex of the chelator 4-[(1,4,8,11-tetraazacyclotetradec-1-yl)-methyl]benzoic acid was demonstrated at physiological pH as well as under acidic conditions. The chelating agent was conjugated to AB35, a monoclonal antibody directed against CEA, without a significant loss of immunoreactivity. The conjugate could, under optimal labeling conditions, be labeled with 67Cu in acetate buffer with a full occupancy of ligands within 20 min. This radiolabeled conjugate showed no t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…Numerous chelators have been reported for complexing copper [5][6][7][8][9][10][11][12][13][14][15][16] and several of these have been functionalized to allow attachment to antibodies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and are now commercially available. The choice of antibody/BFC combination will affect efficacy as an imaging or therapy agent.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous chelators have been reported for complexing copper [5][6][7][8][9][10][11][12][13][14][15][16] and several of these have been functionalized to allow attachment to antibodies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and are now commercially available. The choice of antibody/BFC combination will affect efficacy as an imaging or therapy agent.…”
Section: Introductionmentioning
confidence: 99%
“…Additional advantages to these favorable physical characteristics of the 67 Cu nuclide include the availability of copper chelators with high in vivo stability and the existence of simple and convenient procedures for labeling anti-tumor antibodies. [1][2][3][4][5][6] During the course of preclinical and clinical studies with radiocopper labeled mAbs it was found as an additional benefit, that the biological properties of copper labeled Abs and their metabolites lead to higher tumor uptake and prolonged residence time at the tumor, compared with radioiodinated mAbs. 7,8 Clinical studies with 67 Cu-labeled antibodies have been performed with intact mAbs both at diagnostic and therapeutic levels and indicated that some of the advantages observed in preclinical work with tumor bearing mice, such as improved tumor/blood ratios and higher mean tumor uptake compared with the radioiodinated counterpart, translate to the patient situation.…”
Section: Introductionmentioning
confidence: 99%
“…Current techniques for preparing Fab' fragments necessitate purification steps that may cause irreversible damage to the antigen-binding sites due to denaturation of the antibody [16,17] . For several conjugation methods of antibody fragments and other molecules, such as glutaraldehyde and periodate methods, some active groups or linking agents have to be introduced to the Fab' fragments before they are conjugated to the other molecules [9,[18][19][20] . These steps may further destroy the immunoreactivities of the Fab' fragments.…”
Section: Discussionmentioning
confidence: 99%